ANALISIS PENGARUH PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI KOTA SUKABUMI TAHUN 2020-2023 - amelia, mita (Yayasan Baitul Hikmah al-Zain, 2024)
This study aims to determine the effect of economic growth on poverty reduction in Sukabumi City in 2020-2023. The method used in this article is a qualitative method with a literature study or commonly referred to as a library study or Library Research. The data used is secondary data from the period obtained from the Sukabumi City Statistics Agency. The results showed that economic growth had no significant effect on poverty. The results of the analysis stated that the development and economic growth in Sukabumi City in the percentage of economic growth from 2020-2023 the highest was in 2022, namely 5.35% and the lowest was in 2020, namely -1.48%. Based on the development of poverty in Sukabumi City, the highest percentage of poverty in 2020-2023 was in 2021, namely 8.25% and the lowest in 2023, namely 7.50%.